Polemik Dana Pendidikan di Era Covid -19 Bagi Masyarakat Menengah ke Bawah - Heri Irawan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to determine the source of education funds from parents in the Covid-19 era. This research was conducted using qualitative methods, with the type of case study research, where data collection used interview, observation and documentation techniques, using primary and secondary data sources that according to the research title. The discussion in this study is focused on the problems of the lower middle class in providing education funds and managing education funds. Interviews were conducted on several respondents, and the results of the interviews were analyzed to obtain emic data and ethical data as a result of the research. The results of the research include: the problems faced by the lower middle class community, namely the inability to provide school fees to their children, while for the management of sources of public education funds, they use assistance from the government and manage personal funds into small home-based businesses.